Productive and Reproductive Performances of Indigenous Lime and Parkote Buffaloes in the Western hills of Nepal - Shah, M. K.; Hayashi, Y.; Kumagai, H. (Journal of Buffalo Science, 2016)
Livestock is an integral part for the most rural livelihoods in Nepal. A very high proportion of poor and marginalized farmers depend on livestock as main or supplemental resources for their income. Cattle and buffalo contribute to more than 70% of the livestock sector. The Lime, Parkote and Gaddi are the indigenous buffalo breeds of Nepal. The productive and reproductive performances of indigenous buffalo breeds, Lime and Parkote, were studied in Regional Agricultural Research Station (RARS), Lumle in Nepal. The lactation data of the indigenous buffaloes recorded by RARS livestock farm for 14 years (from 2000 to 2014) was collected and analyzed to assess the production and reproduction traits. The productive performance was 964.0±33.0 litre/lactation in Lime and 878.5±66.3 litre/lactation in Parkote, while a daily milk yield of Lime was 3.2±0.1 litre/day and that of Parkote was 2.9±0.2 litre/day. The milk constituents of Lime were 9.0% fat, 9.2% solids not fat (SNF) and 3.8% protein. The milk contents of Parkote were 8.9% fat, 9.8% SNF and 4.0% protein. The maximum mating was found in October (30%), while the minimum mating was in June (1%) in both the breeds. The calving time of Lime and Parkote was maximum in September (36%). The Lime and Parkote buffaloes are high potential milking animals in the western hills of Nepal. Furthermore, the value chain and organic production approaches would be very useful for the conservation and utilization of these indigenous buffaloes